Designing and implementing a cloud-hosted SaaS for data movement and sharing with SlapOS. (1st January 2014) - Saad, Walid; Abbes, Heithem; Jemni, Mohamed; Cérin, Christophe
For over a decade, the data requirements of e-Science applications increase drastically with the emergence of data-intensive applications. Several tools and frameworks have been developed to manage and handle the big amount of data for the grid platforms. However, the use of these tools by the basic scientist and the grid computing community is not well adopted because of the complexity of the installation and configuration processes. Recently, an open source distributed operating system for clouds emerged, namely SlapOS. The aim of SlapOS is to hide the complexity of IT infrastructures and software deployments from users. In this work, we propose a cloud-hosted data grid using the SlapOS cloud. Through a software as a service (SaaS) solution, users can request and install automatically any data movement and sharing tools like Stork and Bitdew without any intervention of a system administrator. The entire solution is now running in production into the SlapOS cloud at Paris 13 University. Intensive experiments have been conducted on the Grid '5000 testbed to validate our approach.